Web-based service for collaborative authoring learning using grid portal - Hamid, D. H. T. A. H. (IGI Global, 2014)
The OER is a comparatively innovative phenomenon which perhaps seen as a part of a bigger movement towards openness in advanced education including more familiar and recognized trends, for example Open Access (OA) and Open Source Software (OSS). This study introduces a web based service for collaborative authoring learning to create, share and explore dynamic contents since many problems occurred while using the current e-learning software such as Moodle and LAMS. This paper proposed the alternative e-learning software technology based on grid portal, grid computing platform and it was implemented in two courses. The conventional web based education may not suitable for collaborative tools and online collaborative authoring environment because of slow operation in searching, uploading, visualizing output, and file sharing. The new web based service offers an efficient authoring infrastructure dealing with online collaborative tools and collaborative authoring environment based on grid portal technology to solve the unequal distribution of task and compensation problem as well as investigates how to improve access and usefulness for the users of such OER. UCLA Grid Portal open source software with parallel computing system has been implemented in order to design the efficient authoring infrastructure and to implement an online graphics, animation, audio and video technology courses. The idea is to show how the environment can offer web assisted education that goes beyond providing digital learning materials. The OER, especially in the collaborative authoring activity environment in parallel computing are designed to provide students with new environment where they can share skills, knowledge, and understanding within the group members as well as to enhance students' teamwork skills in parallel and distributed processing for high performance computing. Based on the strong foundations, hopefully the users are ready to apply their knowledge, creativity and leadership to fulfill the need of their future career development. As a conclusion, the collaborative authoring learning becomes more effective in terms of performance evaluations analysis.